ANALISIS FAKTOR PENGHAMBAT EKSPOR BAGI UKM Small and Medium Enterprise’s Export Barrier Factor Analyses - Elvia Ivada; Sri Sumaryati; Nurhasan Hamidi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2014)
The intention of this research are to analyze Small and Medium Enterprises’ export barriers in Solo Raya (Surakarta, Boyolali, Sukoharjo, Karanganyar, Wonogiri, Sragen, Klaten) and to prove that all indicators which are knowledge barriers, resources barriers, procedurs barriers and exogenous barrier support export barriers as its construct. This research provides a measurement tool for the next export barriers research as wellThis study combines questioner’s statements that were developed by researchers from previous studies in European countries and export obstacle expressions suggested by Indonesian’s expert. Using Small and Medium Enterprises in Solo Raya region as its respondent sample, and we can collect 400 respondent of SME. There was no such researches in Indonesia before, thus this is the first study using export barrier’s questioner. That’s why Structural Equation Modelling (SEM) is used to provide all construct variables and their indicators become acceptable as a measurement tool for this kind of research. When the researcher run the data using SEM, it showed that construct variables can support the model. In other words, the model does fit the datas. Except for the exogenous barriers that don’t have significant influence to other two barrier which are resources and procedures.